Screening of Rhizobacteria as a Biological Control Agents Against Meloidogyne spp - Ollyvia Eswinda Santi (Faculty of Agriculture, 2024)
Meloidogyne spp. (root-knot nematode are among the most damaging nematode in agriculture estimated $100 billion yieldloss. In Indonesia root-knot nematode can cause damage plant crops up to 40%. Traditionally, the widely used chemichal pesticide to control nematode infestations. Chemical pesticide can increase soil pollution decline soil fertility and hazardous to environmental, animal and human health. Potential of biological control effectively manage the nematode populations, environmental friendly and economically viable for a long period. Biological control can be effective to controlling plant pathogen such as root-knot nematode. Controling root-knot nematodes using alternative way to decrease the number of chemichal pesticides. Moreover, biological control agents promotes beneficial organism, protect the environment, and compatible with other strategy co control the nematode population. The other hand, the growth of biological control agents depends on environmental factor such as humidity, and temperature. In addition, developing biological control takes a lot of maintenance. Rhizobacteria widely recorded that produces substance to protect the soil from pathogen. The capability of rhizobacteria provides nutrients and produce toxin can caused of damaged nematode.
februari 2026 Rudi H
Keywords: Screening of Rhizobacteria; Biological Control; Against Meloidogyne